A Strategy for Implementing a New Elementary Science Instruction Program. - Okey, James R.; Piper, Martha K. (Science Education)
The article focuses on the strategy for implementing a New Elementary Science Instruction Program. There are many reasons why science teachers depend largely upon textbook teaching strategies, but the three most common and all-encompassing are the implementation of a new instructional program does not consider teacher needs, there is a lack of administrative support for the implementation of a new program, and systems to maintain the newly implemented program are inadequate. Part of the strategy includes the priority that should be given to teacher attitudes, availability and maintenance of resources, materials, and equipment, and in-service activities.